Myeloid liver kinase B1 contributes to lung inflammation induced by lipoteichoic acid but not by viable Streptococcus pneumoniae - Pereverzeva, Liza; Otto, Natasja A.; Roelofs, Joris J. T. H.; de Vos, Alex F.; van der Poll, Tom (Respiratory research, 2022)
Background Liver kinase B1 (Lkb1, gene name Stk11 ) functions as a tumor suppressor in cancer. Myeloid cell Lkb1 potentiates lung inflammation induced by the Gram-negative bacterial cell wall component lipopolysaccharide and in host defense during Gram-negative pneumonia. Here, we sought to investigate the role of myeloid Lkb1 in lung inflammation elicited by the Gram-positive bacterial cell wall component lipoteichoic acid (LTA) and during pneumonia caused by the Gram-positive respiratory pathogen Streptococcus pneumoniae ( Spneu ). Methods Alveolar and bone marrow derived macrophages (AMs, BMDMs) harvested from myeloid-specific Lkb1 deficient ( Stk11 -ΔM) and littermate control mice were stimulated with LTA or Spneu in vitro. Stk11 -ΔM and control mice were challenged via the airways with LTA or infected with Spneu in vivo. Results Lkb1 deficient AMs and BMDMs produced less tumor necrosis factor (TNF)α upon activation by LTA or Spneu. During LTA-induced lung inflammation, Stk11 -ΔM mice had reduced numbers of AMs in the lungs, as well as diminished cytokine release and neutrophil recruitment into the airways. During pneumonia induced by either encapsulated or non-encapsulated Spneu , Stk11 -ΔM and control mice had comparable bacterial loads and inflammatory responses in the lung , with the exception of lower TNFα levels in Stk11 -ΔM mice after infection with the non-encapsulated strain. Conclusion Myeloid Lkb1 contributes to LTA-induced lung inflammation, but is not important for host defense during pneumococcal pneumonia.